Toward a New Community of Care: Best Practices for Educators and Administrators During the COVID-19 Pandemic - Cody M. Clemens; Tomeka M. Robinson (Central States Communication Association, 2021)
The onset of COVID-19 left people feeling unsettled, confused, and afraid of what tomorrow may hold. As university professors specializing in health communication, we too were left with these same feelings. As health communication scholars, we focus on issues surrounding illness, risk, crisis, care, health inequities, and wellness. COVID-19 is a health crisis, yes, but it has also changed the way we operate not only in higher education but in daily life. We begin this essay with an overview of COVID-19 and its impact on students, educators, and administrators. Then, we suggest four best practices to foster a community of care in the classroom during and beyond the COVID-19 pandemic.